The impact of social support networks on maternal employment: A comparison of West German, East German and migrant mothers of pre-school children - Mareike Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Given shortages in public child care in Germany, this paper asks whether social support with child care and domestic work by spouses, kin and friends can facilitate mothers' return to full-time or part-time positions within the first six years after birth. Using SOEP data from 1993-2009 and event history analyses for competing risks, the author compares the employment transitions of West German, East German and migrant mothers of pre-school children. The results indicate that West German and migrant mothers return to work sooner if they have access to kin, and that kinship support is particularly important when public child care is unavailable. Furthermore, West German and migrant mothers are more likely to work full-time if their spouses partipate in domestic work. In contrast, social support does not affect employment transitions in East Germany where public child care is more easily accessible and continuous female employment is a prevalent social norm.
Keywords: 330; maternal employment; child care; social support; Mütter; Berufliche Integration; Weibliche Arbeitskräfte; Arbeitsverhältnis; Kinderbetreuung; Soziales Netzwerk; Migranten; Deutschland; Alte Bundesländer; Neue Bundesländer